Artificial Intelligence And Virtual Space In The Information Society: Dialectic Of Social Processes - Bekzod Muhammadiyev (Periodica Journal, 2025)
In the context of an information-based society, the rapid development of artificial intelligence and the expansion of virtual space have become decisive factors shaping contemporary social processes. This article examines the dialectical relationship between artificial intelligence and virtual environments and their influence on social structures, social interactions, and collective consciousness. Particular attention is paid to the ways in which artificial intelligence technologies embedded in virtual platforms transform communication patterns, social behavior, cultural practices, and mechanisms of social regulation. The study also analyzes the contradictory nature of these processes, highlighting both the constructive potential of artificial intelligence in enhancing social efficiency and participation, and the risks associated with digital dependency, social alienation, ethical challenges, and information manipulation. Using a socio-philosophical and interdisciplinary approach, the article reveals the dynamic interaction between technological innovation and social development, emphasizing the need for balanced strategies to regulate artificial intelligence and virtual space in order to ensure sustainable and human-centered social progress.
Keywords: Information society; artificial intelligence; virtual space